ANALISIS EFEKTIVITAS PENGGUNAAN BAHASA ISYARAT DALAM PEMBELAJARAN ANAK TUNARUNGU DI SLB NEGERI BEKASI - Ira Restu Kurnia; Asma Zakiyah; Devi Irviani Wulandari; Komala Sari; Nani Assyifa Putri (STKIP Subang, 2024)
The education of deaf children presents unique challenges, especially in communication and social interaction. This research aims to analyze the effectiveness of sign language in improving the learning experience of deaf students at SLB Negeri Bekasi. This research uses a qualitative method, which is by conducting observations as observations of deaf students in carrying out learning and conducting interview sessions with teachers related to the students observed. The research focused on a sample of two fourth graders and two first graders, to explore their learning experiences and methods related to the use of sign language in the classroom. The main stages of the research included identifying barriers to effective implementation of sign language and developing strategies to increase its use in educational settings. Findings show that sign language significantly facilitates communication, allowing students to express their thoughts and feelings more effectively, which in turn improves their social interactions and academic performance. The study also highlights the importance of customized teaching methods that incorporate sign language to meet the specific needs of children with hearing loss. In conclusion, the research underscores the need to integrate sign language into the curriculum to foster an inclusive learning environment, which ultimately contributes to the academic and social development of children with hearing loss.